Serratia marcescens KMITL2020 as a plant growth stimulant and bacterial antagonist to control brown leaf spot of rice caused by Drechslera oryzae - Soytong, K.; Unthuraloet, K.; Younes Rezaee Danesh (International Journal of Agricultural Technology, 2020)
Serratia marcescens KMITL2020 proved to be growth stimulat and antagonistic to Drechslera oryzae causing brown leaf spot of rice caused by Drechslera oryzae. The brown leaf spot disease was isolated the causal agent which identified as Drechslera oryzae. Bi-culture test between D. oryzae and S. marcescens KMITL2020 inhibited spore production of the tested pathogen 44.12 %. It showed that crude extract from S. marcescens KMIT2020 gave effectively against D. oryzae which the effective dose (ED50) was 92.57 µg/ml. Result showed crude extract from S. marcescens and carbendazim treatments significantly controlled brown leaf spot caused by D. oryzae which reduced the disease of 25 % when compared to the non-treated control in 28 days. Plant growth parameters revealed that crude extract from S. marcescens gave significantly higher tillers, plant height, plant fresh weight, root fresh weight, plant dried weight, root dried weight than carbendazim treatment when compared to the non-treated control.